Language learners' writing attitude and descriptive written output strategies-based instruction - Villamarzo, Perla Caloza- (2007)
The effect of Strategies-based Instruction (SBI) on language learners' writing attitude and descriptive written output was investigated in this study. It is underpinned by Krashen's Input and Affective Filter Hypotheses, Lev Vygotsky's Socio-cultural theory, and supported by insights from Second Language Acquisition, Communicative Language Teaching, Learner-centered Curriculum, Process vs Product Approach in writing, and researches and studies on learning strategies. 140 first year high school students belonging to 4 different sections in the only public high school in the city of Santa Juan participated in the study. It was revealed that SBI had a positive effect on the writing attitude of the students. Improvement in their writing attitude was independent of the writing attitude and length of experience in English teaching of their teachers. It was recommended that teachers be given strategy training in their pre-service and in-service training programs.
Thesis (Ph. D. Education : Language Education)--University of the Philippines, Diliman.
Keywords: High school students' writings; English language -- Writing; Learning strategies -- Philippines -- San Juan City; High school students -- Philippines -- San Juan City -- Attitudes